Effect of A-PRF Application on Palatal Wound Healing after Free Gingival Graft Harvesting: A Prospective Randomized Study - Sousa, Filipa; Machado, Vanessa; Botelho, João; Proença, Luís; Mendes, José João; Alves, Ricardo (European Journal of Dentistry, 2020)
Objective The aim of this study was to investigate the healing effect of advanced platelet-rich fibrin (A-PRF) clot membranes in palatal wounds, resulting from free gingival graft (FGG) harvesting, on the reepithelization rate and on the pain experience after surgery.Materials and Methods Twenty-five patients requiring FGG have participated in this prospective cohort study. After FGG harvesting, the test group (n = 14) received A-PRF clot membranes at the palatal wound and the control group (n = 11) received a gelatin sponge. Epithelialization rate of the palatal wound, wound healing area, correspondent percentage of reduction, and postsurgical pain experience were assessed at 2, 7, 14, 30, and 90 days.Results A-PRF group had higher palatal wound reduction than the control group, at 7, 14, and 30 days of follow-up. The highest difference between the groups was attained at 30 days (91.5% for A-PRF vs. 59.0% control group). At 14 days, a significant difference in the proportion of patients showing total epithelization was found: 64.3% for A-PRF versus 9.1% for the control group. At 90 days, both groups showed total recovery. The control group experienced higher pain level and discomfort until the 14th day, being notably higher on the second day.Conclusion The results suggest that A-PRF membranes haste the healing process, and promote greater reduction along the recovery period and less painful postoperative period.
Keywords: advanced platelet-rich fibrin; biomaterials; free gingival graft; pain; wound healing